First structural evidence of a Se–Br–Br halogen-bonded molecular complex. (18th April 2017) - Torubaev, Yury V.; Skabitskiy, Ivan V.; Pavlova, Alina V.; Pasynskii, Alexander A.
Abstract : Bromination of the bicyclic selenoether (2, 6-dibromo-9-selenabicyclo[3.3.1]-nonane) affords the products ranging from the unique molecular complex C8 H12 Br2 Se–Br2 to the ionic polybromide complex [C8 H12 Br2 SeBr + ]Br5 . Abstract : The halogenation of 2, 6-dibromo-9-selenabicyclo[3.3.1]-nonane1 with 1 equivalent of molecular dihalogens (Br2 and I2 ) afforded a 1 : 1 molecular complex1 –X2 (X = Br (2 ); X = I (3 )), while an excess of Br2 resulted in the ionic species [C8 H12 Br2 SeBr]Br5 − (4 ). X-ray crystallographic data and the nature of Se⋯Br non-covalent bonding in the solid state and solution is discussed.